ANALISIS CAMPUR KODE (MIXING CODE) DAN ALIH KODE (CODE SWITCHING) DALAM PERCAKAPAN BAHASA ARAB (Studi pada Mahasiswa Prodi Pendidikan Bahasa Arab IAIM NU Metro Lampung) - erni zuliana (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
Analysis of Mixed Code (Mixing code) and Transfer Code (Code Switching) in Arabic Conversation (Studies in Student of Arabic Education department IAIM NU Metro Lampung). Lecturer Research of Institute of Islamic Studies Ma’arif NU Metro Lampung in 2016. One of the fundamental problems underlying the author's take on this study, because students majoring in Arabic education is a subject which is still new in IAIM in mid April 2016 the first alumni of Arabic education department IAIM had been graduated, IAIM recently graduated 12 students, so the language skills of students are still very limited, besides that the educational background of the student previously also varied so that the level of language skills of the students vary, so it is sometimes difficult to implementt Arabic actively both oral and written. Therefore, the application of the Arabic language in IAIM is very important, so that students are able to use the Arabic language correctly and well to create language environment (Bi'ah Lughowiyah), by formulating the two issues; First, What is the form of code switching and code-mixing that occurs in the process of group discussion among PBA student in IAIM. Second; Are the factors that cause the occurrence of code switching and code-mixing in the process of group discussion on student PBA. The discussion in this study is qualitative. Data collection methods used in this study is